Performance Analysis of Active Power Filter for Harmonic Compensation using PI-PSO - Thajeel, Ekhlas Mhawi; Hamdan, Daniyal; M. H., Sulaiman (Asian Research Publishing Network (ARPN), 2015)
In the recent decades, the world has seen an expansion in the use of non-linear loads. These loads draw harmonic non-sinusoidal currents and voltages in the connection point with the utility and distribute them through it. A Shunt Active power filters (SAPF) have been proposed as efficient tools for power quality improvement and reactive power compensation. The simulated system is a three phase balanced voltage system with nonlinear load .A particle swarm optimization (PSO) is implemented to optimize the gains of a proportional-integral (PI) algorithm to control the SAPF. The control of the DC voltage of the APF is of great importance. The DC voltage passes by a transient after load variation. This transient is a function of the controller parameters and the load variation. The aim of this work is to determine if the control schemes will be able to adapt to the changing conditions. Different studied for SAPF are implemented in MATLAB\Simulink and results are tabulated and discussed. Results show that the proposed filter can effectively reduce harmonics while keeping its DC-link balanced.